The meaning of animal well-being for farmers and dairy farm employees - Axelsson, Louise; Arvidsson – Segerkvist, Katarina; Pálsdóttir, Anna María; Ljung, Magnus (Agricultural and Food Science, 2024)
Dairy farms in Sweden have undergone a structural change. The number of family farms has decreased, while the number of large dairy farms with employees caring for the animals has increased. This changing situation has created a new farming landscape. From that perspective, it is crucial to gain insight into what factors contribute to the well-being of humans and animals on big dairy farms. Twenty-three semi-structured interviews were conducted on three farms. Farmers and employees were interviewed. The material was analysed using a qualitative approach inspired by qualitative content analysis. For the farmers and employees, animal well-being was central for various reasons and from different perspectives. Despite the differences, the impact of animal well-being was interlinked between the two groups. An increased and deeper understanding of the different perspectives and needs arising from the different roles of farmers and employees can provide new knowledge about factors important for improving animal well-being.